2014
DOI: 10.7314/apjcp.2014.15.22.9655
|View full text |Cite
|
Sign up to set email alerts
|

Roles of p53 and Caspases in Induction of Apoptosis in MCF-7 Breast Cancer Cells Treated with a Methanolic Extract of Nigella Sativa Seeds

Abstract: Background: Nigella Sativa (NS) is an herb from the Ranunculaceae family that exhibits numerous medicinal properties and has been used as important constituent of many complementary and alternative medicines (CAMs). The ability of NS to kill cancer cells such as PC3, HeLa and hepatoma cells is well established. However, our understanding of the mode of death caused by NS remains nebulous. The objective of this study was to gain further insight into the mode and mechanism of death caused by NS in breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 34 publications
2
20
0
2
Order By: Relevance
“…The study by Zu et al and our study provide similar results for alternative candidate drug molecules on the industrial area. Alhazmi et al (2014) examined molecular mechanism of NS induced apoptosis in MCF-7cell line. 29 Casp-3, Casp-8,Casp-9 and P53 gene expression changes were determined by dose-and time dependent NS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Zu et al and our study provide similar results for alternative candidate drug molecules on the industrial area. Alhazmi et al (2014) examined molecular mechanism of NS induced apoptosis in MCF-7cell line. 29 Casp-3, Casp-8,Casp-9 and P53 gene expression changes were determined by dose-and time dependent NS.…”
Section: Discussionmentioning
confidence: 99%
“…Alhazmi et al (2014) examined molecular mechanism of NS induced apoptosis in MCF-7cell line. 29 Casp-3, Casp-8,Casp-9 and P53 gene expression changes were determined by dose-and time dependent NS. The expression levels of Casp-3, Casp-8, Casp-9 and P53 in MCF-7 cells treated with 100 μL/mL NS for 48 h markedly increased by 17.37, 4.82, 10.06 and 6.48 fold when compared with control untreated cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, a supercritical CO 2 extract of black cumin exhibited pro-apoptotic and anti-metastatic effect on MCF-7 cells in vitro [224]. Another study pointed out that the antiproliferative (IC 50 = 62.8 μL/mL) and pro-apoptotic effects of black cumin extract were through mediating both the p53 and caspase pathways [225].…”
Section: Black Cuminmentioning
confidence: 99%
“…Citrus fruit polysaccharides in vitro inhibiting angiogenesis and cell migration [113] Nutrients 2017, 9, 728 [141] jamun fruit NA in vitro inhibiting proliferation and inducing apoptosis [142] cranberry NA in vitro inducing apoptosis and G1 phase arrest [143] Nutrients 2017, 9, 728 [189][190][191] in vitro -inducing cell cycle arrest -lowering the invasive and metastatic potential -stimulating the expression and secretion of IFNγ [192][193][194][195][196][197] red beetroot betanin in vitro showing a dose-dependent cytotoxic effect [198] Nutrients 2017, 9, 728 inhibiting invasion by reducing MMP-9 expression via blockade of NF-κB activation [204] inhibiting invasion by suppressing invadopodium formation and MMP activity [205] inhibiting growth and sustainability of spheroid generated from adherent breast cancer cells [206] ginger 6-dehydrogingerdione in vitro inducing apoptosis and cell cycle arrest in G 2 /M phase [207] garlic diallyl disulfide in vitro inducing apoptosis though: -inhibition of histone deacetylation -inhibition of ERK and the activation of the SAPK/JNK and p38 pathways [216,217] in vitro and in vivo inhibit proliferation and metastasis via: -suppression of the SRC/Ras/ERK pathway -inactivation of the β-catenin signaling pathway [218,219] garlic diallyl trisulfide in vitro and in vivo inducing apoptosis though: -overproduction of ROS and subsequent activation of JNK and AP-1 -upregulating FAS, Bax and p53, and down-regulating Akt and Bcl-2 [220,221] in vitro -inhibiting migration and invasion; -inhibiting ER-α -decreasing protein level of FoxQ1 [213,222,223] garlic S-allyl mercaptocysteine in vitro inducing mitochondrial apoptosis and cell cycle arrest [214] garlic allicin in vitro inhibiting invasion and metastasis [215] black cumin extracts in vitro inducing apoptosis and inhibiting metastasis [224,225] black cumin thymoquinone in vitro and in vivo inducing apoptosis through: -inhibiting Akt phosphorylation -inducing p38 phosphorylation via ROS generation …”
Section: Synergistic Effects Of Dietary Natural Products With Anticanmentioning
confidence: 99%
“…Apoptosis that occurs through different ways can be enhanced in cells. First, candidate molecules suppress the proliferation of malignant cells, and apoptosis increases thereafter and shows a mechanistic approach to cancer chemoprevention and chemotherapy (Alhazmi et al, 2014). In an article by Singh et al published in 2013, the cell death ratio of human lung carcinoma was determined after 25-100 µM usnic acid application for 24 and 48 h. They observed that usnic acid induced mitochondrial membrane depolarization and showed approximately twofold change in apoptotic cells as regards flow cytometry analyses (Singh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%